Critical perspectives on Indo-Caribbean women's literature - Mahabir, Joy A. I. 1966-; Pirbhai, Mariam, 1970- (Routledge research in postcolonial literatures ;, 2013)
"This book is the first collection on Indo-Caribbean women's writing and the first work to offer a sustained analysis of the literature from a range of theoretical and critical perspectives, such as ecocriticism, feminist, queer, post-colonial and Caribbean cultural theories. The essays not only lay the framework of an emerging and growing field, but also critically situate internationally acclaimed writers such as Shani Mootoo, Lakshmi Persaud and Ramabai Espinet within this emerging tradition. Indo-Caribbean women writers provide a fresh new perspective in Caribbean literature, be it in their unique representations of plantation history, anti-colonial movements, diasporic identities, feminisms, ethnicity and race, or contemporary Caribbean societies and culture. The book offers a theoretical reading of the poetics, politics and cultural traditions that inform Indo-Caribbean women's writing, arguing that while women writers work with and through postcolonial and Caribbean cultural theories, they also respond to a distinctive set of influences and realities specific to their positioning within the Indo-Caribbean community and the wider national, regional and global imaginary. Contributors visit the overlap between national and transnational engagements in Indo-Caribbean women's literature, considering the writers' response to local or nationally specific contexts, and the writers' response to the diasporic and transnational modalities of Caribbean and Indo-Caribbean communities"--